Urinary phthalate metabolite concentrations are negatively associated with follicular fluid anti-müllerian hormone concentrations in women undergoing fertility treatment. (December 2021) - Sacha, Caitlin R.; Souter, Irene; Williams, Paige L.; Chavarro, Jorge E.; Ford, Jennifer; Mahalingaiah, Shruthi; Donahoe, Patricia K.; Hauser, Russ; Pépin, David; Mínguez-Alarcón, Lidia
Highlights: Exposure to phthalates has previously been linked to worsened IVF outcomes. Increased urinary phthalates were associated with decreased follicular fluid AMH. Phthalate exposure may accelerate follicular recruitment, lowering ovarian reserve. Abstract: Exposure to phthalates, endocrine-disrupting chemicals commonly used as plasticizers and in consumer products, has been associated with infertility and premature ovarian failure. Our objective was to investigate whether urinary phthalate metabolite concentrations were associated with pre-ovulatory follicular fluid (FF) anti-müllerian hormone (AMH) concentrations in women undergoing fertility treatment. This cross-sectional analysis included 138 women with urinary phthalate data available in the Environment and Reproductive Health (EARTH) Study (2010–2016) in whom FF AMH concentrations were quantified using a sandwich enzyme-linked immunosorbent assay (ELISA). We also quantified 8 phthalate metabolite concentrations using tandem mass spectrometry in 1–2 urine samples per cycle (total 331 urines) and calculated the cycle-specific geometric mean for each metabolite. We applied cluster-weighted generalized estimating equation models (CWGEE) to evaluate the associations of tertiles of urinary phthalate metabolite concentrations with log-transformed FF AMH concentrations adjusting for potential confounders. Study participants had median age of 34.0 years (IQR 32.0, 37.0), 83% were white, and median BMI of 23.1 kg/m 2 (IQR 21.2, 26.1). The following stimulation protocols were used: luteal phase agonist (70%), antagonist (14%), or flare (16%). Urinary concentrations of select phthalate metabolites were negatively associated with FF AMH. For example, women whose urinary mEOHP was in the lowest tertile (range 0.30–4.04 ng/ml) had an adjusted mean FF AMH of 0.72 ng/mL (95% CI = 0.36, 1.44), compared to women in the highest tertile (range 9.90–235), who had an adjusted mean of 0.24 ng/mL (95% CI = 0.12–0.48, p < 0.05). The negative association between urinary concentrations of certain phthalate metabolites with FF AMH concentrations may have implications for antral follicle recruitment and fertility treatment outcomes.